Shunt DC motor speed control methods using MATLAB / Umair Rafeeq Muhammad - Muhammad, Umair Rafeeq (2010)
This thesis focused on three different methods of speed control of Shunt DC motor. The speed of Shunt DC motor was analysed by mean of MATLAB Simulink. The three methods used in this project are field resistance control, armature resistance control and armature voltage control. The torque speed characteristics of Shunt DC motor was analysed with different methods of control mentioned. MATLAB GUI was incorporated in the project to display results obtained. MATLAB GUI is user friendly and a very helpful tool to demonstrate the speed change of Shunt DC motor. The Shunt DC motor simulations were successfully developed and the MATLAB GUI program had been successfully designed.